2016
DOI: 10.1016/j.jpainsymman.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting at the End of Life: A Systematic Review of the Impact of Interpreters on the Delivery of Palliative Care Services to Cancer Patients With Limited English Proficiency

Abstract: Context Language barriers can influence the health quality and outcomes of Limited English Poficiency (LEP) patients at end of life, including symptom assessment and utilization of hospice services. Objective To determine how professional medical interpreters influence the delivery of palliative care services to LEP patients. Methods We conducted a systematic review of the literature in all available languages of six databases from 1966 to 2014. Studies evaluated use of language services for LEP patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 48 publications
6
132
0
Order By: Relevance
“…This is the first Australian study to explore and integrate the experience and perspectives of GPs, interpreters and patients from CALD communities, using FGDs supplemented by semistructured interviews. Our findings reinforce recommendations to engage trained interpreters where doubt exists about patient language fluency, and to follow existing guidelines about working with interpreters, including briefing them prior to consultations (Silva et al., ). It appears, however, that some of the skills required of doctors (such as speaking in short, simple speech turns) are difficult and may need explicit training and supervised practice.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is the first Australian study to explore and integrate the experience and perspectives of GPs, interpreters and patients from CALD communities, using FGDs supplemented by semistructured interviews. Our findings reinforce recommendations to engage trained interpreters where doubt exists about patient language fluency, and to follow existing guidelines about working with interpreters, including briefing them prior to consultations (Silva et al., ). It appears, however, that some of the skills required of doctors (such as speaking in short, simple speech turns) are difficult and may need explicit training and supervised practice.…”
Section: Discussionsupporting
confidence: 81%
“…The considerable benefits of general practitioners (GPs) working with interpreters, especially trained health interpreters, in consultations with patients who have low English proficiency have previously been described (Karliner, Jacobs, Chen, & Mutha, 2007;Leanza, Boivin, & Rosenberg, 2010;Rosenberg, Richard, Lussier, & Shuldiner, 2011;Silva et al, 2016). In Australia, approximately 5% of general practice consultations are in a language other than English (Bayram et al, 2016), and telephone or on-site interpreters can be accessed free of charge to the patient in both general practice and hospital-based consultations (Christine, 2010).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…However, medical interpreting is usually proximate consecutive (PCMI) or over-the-telephone consecutive (remote consecutive medical interpreting [RCMI]) (Gany et al, 2007). Only through new communication training approaches augmented by system-level changes that cultivate simultaneous translation, alongside the use of short phrases, can the clinician-patient relationship be restored to its proper place (Gany et al, 2013;Silva et al, 2015). When HPs describe the patient in the third person to the interpreter, rather than making first person statements directly to the patient, the clinicianpatient relationship has slipped to allow the clinician-interpreter and interpreter-patient relationships to be privileged [24,26], hence the care paradigm is fundamentally altered.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these problems predominate with the consecutive model of language translation. Only through new communication training approaches augmented by system-level changes that cultivate simultaneous translation, alongside the use of short phrases, can the clinician-patient relationship be restored to its proper place (Gany et al, 2013;Silva et al, 2015).…”
Section: Need For Cultural Awareness Trainingmentioning
confidence: 99%
“…Effective interpretation requires language proficiency and mastery of medical terminology in both languages, as well as memory skills, ability to negotiate a three-way conversation, and basic knowledge of cultural customs that can influence health communication (Quan and Lynch 2010). The oncology setting, with its complex information and potential for information overload, can be particularly challenging for interpreters (Butow et al 2012;Perez et al 2016;Silva et al 2016). In prenatal genetic counseling, research has shown that misinterpretation limited comprehension and inhibited development of a trusting relationship (Browner et al 2003).…”
Section: Introductionmentioning
confidence: 99%